Barrett’s esophagus and esophageal adenocarcinoma: biomarkers of proliferation, apoptosis, autophagy and angiogenesis - E. S. Petenyova; A. B. Salmina; S. I. Berdnikov; V. V. Salmin; V. G. Abramov; N. N. Medvedeva; E. V. Semichev (Бюллетень сибирской медицины)
Aim: analysis of all known markers of proliferation, apoptosis, autophagy and angiogenesis in the pathogenesis of Barrett’s esophagus and esophageal adenocarcinoma with the purpose of improvement of diagnostics and  treatment quality.Materials and methods. Analysis of the available scientific sources by Russian and foreign authors.Results. Data on all the known markers has been structured and is supposed to be integrated into clinical practice in the diagnosis and treatment of Barrett’s esophagus and esophageal adenocarcinoma at various stages  of disease development.